Assessing the Psychometric Properties of the Internet Addiction Test (IAT) Among Lebanese College Students - Samaha, Ali A.; Fawaz, Mirna; El Yahfoufi, Najwa; Gebbawi, Maya; Abdallah, Hassan; Baydoun, Safaa A.; Ghaddar, Ali; Eid, Ali H. (Frontiers in Public Health, 2018)
Internet addiction is an emergent problem; yet, both a strong conception of the factors precipitating challenging activities and a gold standard tool for evaluating symptoms are deficient. The aim of this study was to carry out a psychometric analysis using the most commonly employed screening tool, the young Internet Addiction Test (IAT), comprising a sample of Lebanese University medical students. 256 undergraduate medical students from a university in Beirut, Lebanon were included in our IAT. Exploratory factor analysis was employed, and four factors were extracted. These four factors were named as Lack of Control, Social Withdrawal and Emotional Conflict, Time Management Problems, and Concealing Problematic Behavior. Furthermore, the selected factors explained 56.5% of the total variance. Cronbach’s alpha coefficient for the internal reliability of the scale was found to be 0.91. For each subscale, the internal consistency score was approximated and detected as 0.76, 0.74, 0.69, and 0.63 for the first through fourth factor, respectively. Item total correlations were calculated and had a value range from 0.37 to 0.63 for the 20 items. IAT is a proper tool for evaluating internet addiction in Lebanese college students.